PENGARUH KINERJA KEUANGAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MODERASI (Studi Pada Perusahaan Manufaktur Sub Sektor Industri Dasar Dan Kimia Yang Terdaftar Di BEI Tahun 2015-2019) - Alitsa Fatwa; Efni Yulia; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of Financial Performance andOwnership Structure on Firm Value with Corporate Social Responsibility as amoderating variable. By using PER is used to measure the Firm Value variable.ROA is used to measure Financial Performance. Managerial Ownership is usedfor Ownership Structure.The population in this study is the ManufacturingCompanies of the Basic and Chemical Industry Sub-Sectors listed on theIndonesia Stock Exchange (IDX) for the 2015-2019 period, which total 63companies. With a sample of 58 companies.Determination of the sample usingpurposive sampling, the technique of determining the sample with several criteria,namely; Basic and Chemical industry sector companies listed on the IDX from2015-2019., Basic and Chemical industry sector companies that did not publishcomplete financial statements on the IDX from 2015-2019., Basic and Chemicalindustry sector companies Chemicals that do not use Rupiah currency.The resultsshowed that ownership structure on firm value and the effect of ownershipstructure on firm value, moderated by CSR, had no effect on firm value, whilefinancial performance on firm value, CSR on firm value, and financialperformance on firm value, moderated CSR, had an effect on financial andfinancial performance. The value of the company. Keywords: Financial Performance, Ownership Structure, Company Value,Corporate Social Responsibility.